Implementasi Qowa’id Wa Tarjamah Dalam Pembelajaran Bahasa Arab Pada Kelas XI di Madrasah Aliyah Hasyim Asy’ari - Dlikri, Satia; Arini, Aida; Al- Amin, Ahmad Amiq (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2025)
Arabic language learning at Madrasah Aliyah has an important role in developing students' religious language literacy and language skills. At Madrasah Aliyah Hasyim Asy'ari, Arabic is taught as a medium for studying classical books and understanding the Islamic religion through the qowaid wa tarjamah method, which focuses on mastering grammar (nahwu-sharaf) and the ability to translate texts. Although this method is effective in helping students understand the structure of the Arabic language, its application tends to be monotonous and less interactive, thus affecting student motivation and understanding. This research aims to evaluate the implementation of the qowaid wa tarjamah method in class 11 of Madrasah Aliyah Hasyim Asy'ari, identify existing obstacles, and look for innovative strategies to increase learning effectiveness. A descriptive qualitative approach was used to collect data through observation, interviews and documentation. The results showed that although this method helps students understand the structure of the Arabic language, the main challenge is the lack of variety in learning strategies and student engagement. Therefore, innovation is needed such as the use of modern learning media, collaborative learning, and applicable contexts to make learning more interesting and relevant to students' needs. This research is expected to contribute to the development of more effective Arabic language learning methods at Madrasah Aliyah.